Pemanfaatan Video Edukasi Sebagai Upaya Menurunkan Kecemasan pada Pasien Pre Operasi - Achmad Zainullah; Mustika Sari (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Preoperative anxiety is a common issue that can affect a patient's physiological and psychological condition before undergoing surgery. One effective method to reduce anxiety is through proper education, including the use of audiovisual media such as educational videos. This study aims to evaluate the effectiveness of educational videos in reducing preoperative anxiety levels in patients. The method used involves a pre-test and post-test design with an intervention consisting of an educational video about the surgical procedure, patient preparation, and relaxation techniques. The results indicate a significant reduction in patients’ anxiety levels after receiving education through video. Therefore, the use of educational videos can be an effective strategy to enhance patients' mental readiness before surgery and should be widely implemented in healthcare facilities.